Pengaruh Komitmen Organisasi terhadap Kepuasan Kerja yang dimoderasi Keterlibatan Kerja pada BRI Kantor Cabang Kusuma Bangsa - Fahmi Abdillah Maulidyansah (Universitas Negeri Surabaya, 2018)
This study aimed to analyze the influence of organizational commitment on job satisfaction with job involvement as a moderator variable. The sample used in this study around 35 employees, that is all employees of the Bank Rakyat Indonesia Surabaya Kusuma Bangsa Branch Office. However, from 35 sample of employees, only 31 returned. The data analyze technique used in the study is Structural Equation Model Partial Least Square with the help of SmartPLS 2.0 software. The results shows that there is a positive effect between organizational commitment on job satisfaction and job involvement weakens the positive influence of organizational commitment on job satisfaction.